2023
DOI: 10.3390/antiox12030600
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Volatiles (mVOC) Emitted by the Phytopathogen Erwinia amylovora Promote Arabidopsis thaliana Growth and Oxidative Stress

Abstract: Phytopathogens are well known for their devastating activity that causes worldwide significant crop losses. However, their exploitation for crop welfare is relatively unknown. Here, we show that the microbial volatile organic compound (mVOC) profile of the bacterial phytopathogen, Erwinia amylovora, enhances Arabidopsis thaliana shoot and root growth. GC-MS head-space analyses revealed the presence of typical microbial volatiles, including 1-nonanol and 1-dodecanol. E. amylovora mVOCs triggered early signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…In our previous studies, ROS generation and oxidative stress were found as early events for the abiotic elicitation on perylenequinone biosynthesis in Shiraia under the treatment of ultrasound [ 22 ], bamboo charcoal powder [ 42 ] and Triton X-100 [ 43 ]. Parmagnani et al (2023) reported that VOCs produced by Erwinia amylovora enhanced shoot and root growth of Arabidopsis thaliana by triggering ROS burst from few minutes upon exposure [ 44 ]. The mixture of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, ROS generation and oxidative stress were found as early events for the abiotic elicitation on perylenequinone biosynthesis in Shiraia under the treatment of ultrasound [ 22 ], bamboo charcoal powder [ 42 ] and Triton X-100 [ 43 ]. Parmagnani et al (2023) reported that VOCs produced by Erwinia amylovora enhanced shoot and root growth of Arabidopsis thaliana by triggering ROS burst from few minutes upon exposure [ 44 ]. The mixture of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…The applications of AgNPs are focused on different areas of biomedicine, biology, electronics, and agriculture, among others [21]. Currently, applications of AgNPs have become more prominent because of their antibacterial properties [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The "fire blight" bacteria attack buds and flowers, reducing significantly the production of pears and apples around the world. For this reason, E. amylovora has been classified as a quarantine organism in several countries [23,26,27].…”
Section: Introductionmentioning
confidence: 99%